PENGARUH KUALITAS PRODUK, GAYA HIDUP DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE XIAOMI - Efendi, Bahtiar; Ashshiddiqy, Muhammad Zain (DFAME Digital Financial Accounting Management Economics Journal, 2023)
The study aims to find out the impact of product quality, lifestyle, and brand image on Xiaomi smartphone purchasing decisions in FEB students. Data analysis method using double linear regression analysis. Sampling methods use non-probability sampling with purposive samplings. The sample was obtained from the Hair formula of 180 respondents who were FEB Unzil students. The results of this study showed that: (1) Product quality has a positive influence on the purchase decision with thitung value (7,908) > tables (1,973) and significance value (0,000) < (0,05). (2) Lifestyle has a positively influenced on the purchasing decision by thitung (4,832) > ttables (1,973), and significant value (0.000)< (0.05). (0,05).